1998
DOI: 10.1007/bf02920154
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of cellulose using ternary mixtures of purified celluloses

Abstract: The saccharification of microcrystalline cellulose by reconstituted ternary mixtures of purified cellulases (one endoglucanase and two cellobiohydrolases) has been studied over the entire range of mixture compositions. Ternary plots are used to compare the performance of five synthetic mixtures drawn from the cellulase systems of Acidothermus cellulolyticus, Trichoderma reesei, Thermomonospora fusca, and Thermotoga neapolitana. Results reveal that at least one synthetic mixture utilizing enzymes from three dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…Few studies have investigated the synergism among catalytic domains of various bacterial enzymes, and the synergistic interactions between bacterial and fungal hydrolases acting on pretreated lignocellulosic biomass. Some reports have shown exo/exo and exo/endo synergism between fungal and bacterial enzymes hydrolyzing crystalline cellulose [21,22]. Recent publications have reported synergy between Trichoderma and Serratia/Streptomyces based on chitin-degrading hydrolases completely hydrolyzing untreated crab shells [23].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated the synergism among catalytic domains of various bacterial enzymes, and the synergistic interactions between bacterial and fungal hydrolases acting on pretreated lignocellulosic biomass. Some reports have shown exo/exo and exo/endo synergism between fungal and bacterial enzymes hydrolyzing crystalline cellulose [21,22]. Recent publications have reported synergy between Trichoderma and Serratia/Streptomyces based on chitin-degrading hydrolases completely hydrolyzing untreated crab shells [23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that synthetic enzyme mixture (designer combinations) of cellulase enzymes can give relatively higher hydrolysis yields (Ballesteros 2010;Banerjee et al 2010a, b;Besselink et al 2008). Currently, the only reliable method for designing optimal cellulase mixtures involves extensive experimentation using statistically designed combinations of various enzyme levels (Baker et al 1998;Banerjee et al 2010a, b;Berlin et al 2007;Gao et al 2010). Since conducting such large number of hydrolysis experiments is expensive, time-consuming and labor intensive, a comprehensive hydrolysis model that can that can capture process dynamics and predict hydrolysis profile under various scenarios could be an alternate feasible approach.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulases are a subset of the glycosyl hydrolase superfamily of enzymes that have been grouped into more than 100 families based on amino acid sequence similarity, enzyme reaction mechanism, and protein fold motif [5]. Endo-and exo-cellulases are two classes of cellulases that have been shown to be effective in the hydrolysis of cellulose from biomass [6].…”
Section: Introductionmentioning
confidence: 99%